The Effects of Strategic Planning on Common Stock Returns - Kudla, Ronald J. (Academy of Management Journal, 1980)
In a study of the effects of strategic planning, statistical tests did not indicate significant differences between the returns earned by shareholders of planning firms and nonplanning firms. There was indication of a transitory reduction in the riskiness of planning firms after the initiation of planning, relative to nonplanning firms, where risk is measured in a capital asset pricing model framework.